Aminopropyl-modified mesoporous silica nanospheres for the adsorption of Cr(VI) from water - Fellenz, Nicolás Antonio (2015)
Aminopropyl-functionalized mesoporous silica spherical particles were obtained through post-synthetic route. The suitability of this material as an adsorbent for heavy metals from aqueous media was tested by Cr(VI) adsorption experiments performed at various pH conditions, chromium concentrations and time. The synthesized particles were characterized before and after functionalization by X-ray diffraction at low angles,nitrogen adsorption?desorption isotherms, infrared Fourier transform spectroscopy, scanning electron microscopy and thermogravimetric analysis. It was found that Cr(VI) adsorption occurs more efficiently in the pH range between 2 and 3. As a consequence of the nanometer scale of the particles, concentration profiles do not develop inside of them and thus there are no diffusional restrictions within the pores, leading to a higher Cr(VI) adsorption than that previously reported for similar systems. Chromium desorption for material reutilization was carried out in basic media. Results showed that the amino groups were grafted successfully without mesostructure damage. These groups are essential for the metal ion removal and no significant leaching was observed after fouruse/regeneration/use cycles. The batch equilibrium data fitted well the Langmuir isotherm with a maximum adsorption capacity of 87.1 mg/g at 25ºC. A discussion about the relationship between structure and its behavior as adsorbent, including regeneration and reusability, is given.